Nutritional Support Using Enteral and Parenteral Methods. (5th September 2018) - Tadlock, Matthew D; Hannon, Matthew; Davis, Konrad; Lancman, Micah; Pamplin, Jeremy; Shackelford, Stacy; Martin, Matthew; Stockinger, Zsolt
Abstract: The purpose of this Clinical Practice Guideline is to provide an approach for optimal nutritional support in the postinjury period for those injured in combat. Indications and contraindications for enteral and parenteral nutrition are addressed. Timing of nutritional support, nutritional goals, energy requirements, and ideal formula selection for various types of traumatic injuries are addressed. Challenges encountered providing nutrional support for the traumatically injured in the deployed environment are also discussed.